The role of transcriptional regulators in metal ion homeostasis of Mycobacterium tuberculosis - Wang, Shuxian; Fang, Ren; Wang, Hui; Li, Xiaotian; Xing, Jiayin; Li, Zhaoli; Song, Ningning (Frontiers in Cellular and Infection Microbiology, 2024)
Metal ions are essential trace elements for all living organisms and play critical catalytic, structural, and allosteric roles in many enzymes and transcription factors. Mycobacterium tuberculosis (MTB), as an intracellular pathogen, is usually found in host macrophages, where the bacterium can survive and replicate. One of the reasons why Tuberculosis (TB) is so difficult to eradicate is the continuous adaptation of its pathogen. It is capable of adapting to a wide range of harsh environmental stresses, including metal ion toxicity in the host macrophages. Altering the concentration of metal ions is the common host strategy to limit MTB replication and persistence. This review mainly focuses on transcriptional regulatory proteins in MTB that are involved in the regulation of metal ions such as iron, copper and zinc. The aim is to offer novel insights and strategies for screening targets for TB treatment, as well as for the development and design of new therapeutic interventions.